Chemical composition of leaf oils of Myristica beddomeii (King), Myristica fragrans (Houtt.) and Myristica malabarica (Lamk.) - B Krishnamoorthy, T John Zachariah, N K Leela, K M Maya, J Rema, P A Mathew, T M Vipin, (Journal of Spices and Aromatic Crops, 2008)
Essential oil constituents of leaves of three Myristica species namely, Myristica beddomeii, M. fragransand M. malabarica were determined by gas chromatography and gas chromatography-massspectrometry. M. fragrans was dominated by monoterpenes (91%), M. beddomeii contained mono-(48%) and sesquiterpenes(35%) whereas M. malabarica was dominated by sesquiterpenes (73%).The leaf oil of M. beddomeii was dominated by α-pinene (19.59%), t-caryophyllene (14.63%) andβ-pinene (12.46%). The leaf oil of M. fragrans contained sabinene (19.07%), α-pinene (18.04%), 4-terpineol (11.83%), limonene (8.32%) and β-pinene (7.92%) as major compounds, while t-caryophyllene (20.15%), α-humulene (10.17%), nerolidol (9.25%) and δ-cadinene (6.72%) werepredominant in the oil of M. malabarica. Linalool, α-terpineol, t-caryophyllene, β-elemene and γ-elemene were present in all the three species. This is the first report on the essential oil compositionof M. beddomeii leaves.